Frequency and Severity of Phantom Limb Pain in Veterans with Major Upper Limb Amputation: Results of a National Survey. Issue 8 (25th December 2020) - Balakhanlou, Ellie; Webster, Joseph; Borgia, Matthew; Resnik, Linda
Abstract : Objective: To describe the frequency and severity of phantom limb pain (PLP) in veterans with major upper limb amputation and determine the association between PLP and person, amputation, and prosthesis characteristics. Design: Cross‐sectional design. Setting: National survey of veterans living in the community. Participants: U.S. military veterans (N = 776) with major upper limb amputations. Main Outcome Measures: Frequency and intensity of PLP, person characteristics such as age and gender, amputation characteristics such as level and etiology, and prosthesis characteristics such as type and intensity of prosthesis use. Results: Respondents were 97% male with a mean age of 63 years and a mean time since amputation of 31 years. The most common amputation level was transradial (36%) and 62% reported accident as the amputation etiology. 73% of amputees reported PLP with a mean intensity score of 4.2 (standard deviation 3.4). PLP frequency in the daily to always category was reported in 42% of amputees. Weekly and more frequent residual limb pain was associated with having any PLP. Amputation at the shoulder (odds ratio [OR] 3.78 [1.93, 7.39]), amputation at the transhumeral level (OR 1.76 [1.10, 2.81]), and amputation due to cancer (OR 5.33 [1.15, 24.81]) were also associated with any PLP. Moderate (β = 1.34, P = < .001) and severe (β = 3.31, P < .001) residual limb pain intensity was associated with higher PLP intensity among those with pain. Amputation at the shoulder level was associated with a 1.5 points higher average pain intensity score ( P < .001) compared to the transradial level. Multivariable models failed to show an association between PLP prevalence and amputation of the dominant limb ( P = .08) and PLP was not associated with intensity of daily prosthesis use in bivariate analyses. Conclusion: This study of a large cohort of veterans with major upper limb amputation highlights the long‐term persistence of moderate frequency and intensity PLP.